Предмет: Алгебра,
автор: artembelugin2003
Решите пожалуйста!!!(подробно).
Приложения:
Ответы
Автор ответа:
1
решение
= х-5 \ х*( х+5) + х+5 \ х*( х-5) - 4х \ ( х-5)*( х+5) =
(х-5)*(х-5) + (х+5)*(х+5) - 4х^2 \ х* (х-5)* ( х+5) =
х^2-5х-5х+25+х^2+5х+5х+25-4х^2 \ х*( х-5)*(х+5) =
-2х^2+50 \ х*( х^2-25) =
-2*( х^2 - 25) \ х*( х^2 - 25) = -2 \ х
artembelugin2003:
Благодарю очень помог.
Похожие вопросы
Предмет: Английский язык,
автор: Dianaaa0200
Предмет: Химия,
автор: sheschestackowa
Предмет: География,
автор: killmetaniiq
Предмет: Химия,
автор: LenaBelous2002
Предмет: Математика,
автор: исттствучен